2021
DOI: 10.3390/polym13142373
|View full text |Cite
|
Sign up to set email alerts
|

Temperate UV-Accelerated Weathering Cycle Combined with HT-GPC Analysis and Drop Point Testing for Determining the Environmental Instability of Polyethylene Films

Abstract: Polyethylene films are one of the most frequently used packaging materials in our society, due to their combination of strength and flexibility. An unintended consequence of this high use has been the ever-increasing accumulation of polyethylene films in the natural environment. Previous attempts to understand their deterioration have either focused on their durability using polymer analysis; or they have focused on changes occurring during outdoor exposure. Herein, this study combines those strategies into on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…All films containing the additive met this requirement after weathering, whereas the films without the additive showed a drop point above 140°C. This is consistent with the presence of the additive accelerating film degradation and conversion into a wax [ 39 ]. This is evidence that the PAS 9017 : 2020 accelerated test standard does predict aspects of the degradation of PAC plastics in the South of France and Florida.…”
Section: Is There Evidence That Correlates Laboratory Weathering Test...supporting
confidence: 84%
See 4 more Smart Citations
“…All films containing the additive met this requirement after weathering, whereas the films without the additive showed a drop point above 140°C. This is consistent with the presence of the additive accelerating film degradation and conversion into a wax [ 39 ]. This is evidence that the PAS 9017 : 2020 accelerated test standard does predict aspects of the degradation of PAC plastics in the South of France and Florida.…”
Section: Is There Evidence That Correlates Laboratory Weathering Test...supporting
confidence: 84%
“…In the second study [ 39 ], the control sample tested in the South of France showed a 67% M w loss, which exceeded the 27% M w reduction observed for the same control sample in laboratory weathering test using PAS 9017; thus the correlation between artificial and outdoor weathering is less clear in this case. 1.b) The control sample for the Florida test was not included in the second study [ 39 ], so a comparison/correlation between samples cannot be made. 1.c) For the purpose of PAS 9017 more than one replicate is required.…”
Section: Is There Evidence That Correlates Laboratory Weathering Test...mentioning
confidence: 93%
See 3 more Smart Citations